Characteristics of Calorific Value of Briquettes Made From Cymbopogon Citratus Waste As an Alternative Fuel - Nurdin, Hendri; Wagino, Wagino; Sari, Delima Yanti; Siregar, Batu Mahadi (Universitas Negeri Padang, 2022)
Product diversification through Cymbopogon citratus briquettes as an alternative fuel for the development of renewable energy. The waste from the Cymbopogon citratus production process is a potential source of renewable energy that can be used as briquettes. This is an alternative to reduce dependence on fuel oil energy which is the main need for ordinary people. The purpose of developing Cymbopogon citratus waste briquettes with various variances and the use of tapioca adhesive, in obtaining the characteristics of the calorific value of briquettes. The method of making briquettes by using a press and optimizing the composition of the appropriate mixture as an effort to get the calorific value. From this research, the calorific value of Cymbopogon citratus briquettes is 8230.65 kJ/kg at a percentage mixture of 90 : 10 and its density is 394.90 kg/m3. From the acquisition of these characteristic values, it can be recommended as an alternative fuel in an effort to develop renewable energy in the utilization of lemongrass waste.